دراسة صحية للضرع عند الأبقار الجولانية المحلية والمدرجة وأثر ذلك على أدائها الإنتاجي في محافظة القنيطرة - جبلاوي, رفيق; قصقوص, شحادة; المشيعل, حسين (Latakia University Journal -Biological Sciences Series, 2019)
نفذت الدراسة في محافظة القنيطرة خلال عامي 2008 و 2009 لمقارنة الأداء الإنتاجي والمواصفات الصحية للضرع بين الأبقار الجولانية و المدرجة ( فريزيان × جولاني ). قدر خلال موسم الحلابة مؤشرات إنتاج الحليب، التهاب الضرع. بلغت كمية الحليب اليومية (5.36 ± 1.19 مقابل 18.54 ± 4.24 كغ/ يوميا" ) وفي الموسم (1125.6±0.249 مقابل5710،1±1306.1 كغ/موسم ) في الأبقار الجولانية والمدرجة على التوالي. وبينت نتائج الزرع الجرثومي أن المكورات العنقودية والمكورات العقدية والإشريكية القولونية أهم المسببات المرضية في الأبقار المدرجة ولم يلاحظ أي اشتباه لإصابة في الأبقار الجولانية طيلة فترة الدراسة. وبينت النتائج حساسية جميع الجراثيم السابقة تجاه الصادات الحيوية سيبروفلوكساسين و إنروفلوكساسين و للسيفالوسبورين ومقاومة للبنسلين. لوحظ ارتباط سلبي لكن غير معنوي بين إنتاج الحليب الكلي ومستوى الناقلية الكهربائية في الحليب الناتج وبكلا السلالتين الجولانية والجولانية المدرجة ( r = -0.34) والمدرجة ( r = -0.26). This study was conducted in AL-Qunietra District in 2008\2009 to compare the productive performance and health specifications of the udder in Golani and improved Golani cows. The quantity of milk yield was ( 5.36 ± 1.19 compared with 18.54 ± 4.24 kg\ daily ) and lactation yield ( 1125.6 ± 0.249 compared with 5710.1 ±1.1306 kg\ lactation) between the Golani and improved Golani cows respectively. There was no mastitis in the Golani cows. The results of culturing show that Staphylococcus, Streptococcus and E.coli were the important causing organisms of Mastitis and all were sensitive to ciprofloxacin-enrofloxacin and cephalosporin antibiotics, and are resistant to penicillin antibiotic. Negative correlation was noticed, but not significantly, between milk production and the value of electrical conductivity in milk in two breeds، Golani ( r= - 0.34 ) and improved Golani ( r= -0.26 ).